2017
DOI: 10.1002/mp.12015
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative symmetry‐based analysis of hyperacute ischemic stroke lesions in noncontrast computed tomography

Abstract: Purpose Early identification of ischemic stroke plays a significant role in treatment and potential recovery of damaged brain tissue. In non-contrast CT (ncCT), the differences between ischemic changes and healthy tissue are usually very subtle during the hyper-acute phase (<8 hours from the stroke onset). Therefore, visual comparison of both hemispheres is an important step in clinical assessment. A quantitative symmetry-based analysis of texture features of ischemic lesions in non-contrast CT images may prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…Gillebert et al [28] found a slightly higher DSC (0.67) than the present study (0.61 at optimal threshold) for simulated data but reported high variance for performance using actual patient images. Peter et al [29] reported a ROC AUC of 0.82 which was less than that of the present study. At least one infarct detection software has been made commercially available [30].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Gillebert et al [28] found a slightly higher DSC (0.67) than the present study (0.61 at optimal threshold) for simulated data but reported high variance for performance using actual patient images. Peter et al [29] reported a ROC AUC of 0.82 which was less than that of the present study. At least one infarct detection software has been made commercially available [30].…”
Section: Discussioncontrasting
confidence: 91%
“…Sensitivity calculated from Maldjian et al reported values for lentiform nucleus and insula (0.85) lower than the sensitivity calculated over the ASPECTS regions in the present study (0.93). Gillebert et al [28] as well as Peter et al [29] applied a texture and atlas-based approach to lesion segmentation. Gillebert et al [28] found a slightly higher DSC (0.67) than the present study (0.61 at optimal threshold) for simulated data but reported high variance for performance using actual patient images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the gray-level co-occurrence matrix (GLCM)-based tissue texture parameters were significantly different between patients and controls, and the most discriminative feature was angular second moment. In another study of 139 patients with hyperacute ischemic stroke (< 8 h), the authors identified 6 texture features from NCCT images that could differentiate ischemic lesions from their contralateral normal tissue [ 57 ]. The classification model, constructed by 3 supervised machine learning algorithms (i.e., support vector machine, decision trees, and adaboost) achieved an average AUC of 0.82.…”
Section: Applications Of Radiomics In Strokementioning
confidence: 99%
“…While NCCT-based radiomic features have the ability to identify acute infarcted tissue, the information they capture is confined to a part of the lesion in a single slice (2D-radiomics) [ 56 , 57 ]. It is challenging to perform a volumetric assessment for stroke lesions that cannot be visually perceived.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%